2014
DOI: 10.1111/oik.01483
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of information use in breeding habitat selection on the evolution of settlement time

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Schmidt et al. () suggested that clutch predation may prevent phenological shifts in response to climate change. More recently, Harts et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schmidt et al. () suggested that clutch predation may prevent phenological shifts in response to climate change. More recently, Harts et al.…”
Section: Discussionmentioning
confidence: 99%
“…If the fitness costs of arriving in a period with low food abundance and/or high energetic costs are larger than the costs of chicks hatching out of synchrony with their prey, no strong selection for a phenological match between food abundance and hatch date would be expected. Schmidt et al (2015) suggested that clutch predation may prevent phenological shifts in response to climate change. More recently, Harts et al (2016) suggested that a higher predation risk on early arriving individuals may select for later arrival times of migratory birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to claim that high quality breeding sites, to choose the present example, are limiting, but rather, occupancy bias is insufficient. This may reflect both constraints on information gathering (Kokko and Sutherland , Schmidt et al ) and the spatiotemporal structure of the environment, which alters the value of being informed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequencydependent advantage for an individual to preempt space, such as a breeding territory, earlier than its competitors can have a significant impact on both population and evolutionary dynamics (Day and Kokko 2015). For example, Schmidt et al (2015b) showed that such a preemptive advantage results in reduced levels of information gathering commensurate with population size. However, when this preemptive advantage relaxes due to declining demographic rates (e.g.…”
Section: Discussionmentioning
confidence: 99%